The Implementation Strategies of Good Corporate Governance for Zakat Institutions in Indonesia - Irman Firmansyah; Abrista Devi (International Journal of Zakat, 2017)
Zakat institutions are aimed to contribute to poverty alleviation in a country. In order to ensure that the Zakat institutions can perform well, it is urgently needed to have professional good governance. This research is aimed to find the best strategies to improve the management quality of the Zakat institutions in Indonesia. The research method used in this study comprises both qualitative and quantitative approach using Analytic Network Process. The research results show that to enhance the quality of good governance in Zakat institutions, following are the key elements. The top three main priorities in transparency principles are financial report standardization, followed by Zakat distributions transparency, and the knowledge about decision making. The top three main priorities in responsibilities principles are working compliance with SOPs, followed by prudential principles, and Shari'ah compliance. The top three main priorities in accountability principles are the effectiveness of internal control, followed by performance measurement, and competencies compliance with job descriptions. The top three main priorities in fairness principles are giving priority to the common interest, followed by equal treatment for all stakeholders, and prudential principles in asset management. To achieve all these priorities, the main strategy which should be prioritized is independent human management system, followed by having Shari’ah board and audit committee and the computerized Zakat system. Keywords: Zakat institutions, Good Governance, Analytic Network Process JEL Classification: L31, G34